EVOLUTION OF PERFORMING ARTS CENTERS: A HISTORICAL AND CONTEMPORARY ANALYSIS - Gupta, Varnan; Rampal, Tanisha; Naaz, Shaila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper delves into the rich history and transformative journey of performing arts centres from ancient times to the present day and showcases a study of modern design of performing arts centre. Beginning with open-air amphitheaters and ritualistic performances in ancient civilizations, the study traces the development of these centres through medieval courtly settings, the Renaissance period’s architectural innovations, and the emergence of dedicated opera houses and concert halls in the 19th century. Examining the 20th-century shift towards modernist architecture and multipurpose venues, the research highlights the profound impact of technology on the performing arts experience. From gas lighting and improved rigging systems in the 19th century to the integration of cutting-edge audio-visual technologies in the 21st century, the paper explores how these advancements have shaped the design and functionality of performance spaces. Furthermore, the study addresses the societal shifts reflected in the design of performing arts centres, including the emphasis on inclusivity and accessibility in the 21st century. It investigates the contemporary trends of sustainability, flexibility, and the integration of virtual platforms, showcasing how performing arts centres have evolved into dynamic hubs for cultural expression, community engagement, and global connectivity. Through an interdisciplinary lens that considers architectural, technological, and socio-cultural dimensions, this research paper provides a comprehensive overview of the history and present-day transformation of performing arts centres. The findings contribute to a deeper understanding of the dynamic interplay between architecture, technology, and societal values in shaping the landscape of performing arts venues.